Electrostatic pollination of pistachio (Pistacia vera L.) - A novel technique of pollen supplementation in agriculture - Vaknin Y.; Eisikowitch D.; Gan-Mor S.; Bechar A.; Ronen B. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Our aim was to harness electrostatic forces and use them as a method of pollen supplementation in agriculture. We have devised a machine that will electrostatically charge pollen and mechanically convey it to flowers. In field experiments in pistachio Pistacia vera L. in California, during April 1998, we found that electrostatically treated trees young female trees produced 16.2 per cent more fruitlets per cluster, a 11.3 per cent higher yield, 18.6 per cent higher split percentages and 60 per cent lower blank percentages than those which only received drifting pollen from nearby orchards. We conclude that electrostatic pollination of pistachio could replace natural wind pollination and may result not only in higher crops, but also in better quality of the nuts.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)